Moratín y Godoy en la gestión liberal de la memoria histórica española (1820-1900) - Calvo Maturana, Antonio (Cuadernos de Historia Moderna, 2008)
In 1828, the dramatist Leandro Fernández de Moratín was buried in the cemetery of Pére Lachaise, in Paris. Manuel Godoy, the hated First Minister of Charles IV of Spain, has lain in the same place since 1851. They both had to run away from Spain during the reign of Ferdinand VII, and lived in the French exile. Thanks to a Royal Order by Elisabeth II, Moratin’s corpse was moved to a mausoleum in Spain and his memory was honoured. However, his protector, Godoy, is still the Spanish antihero for most of the historians. This essay analyzes the construction of the Spanish memory during the nineteenth century since the establishment of liberalism, a political system which also paid tribute to other artists protected by Godoy and exiled in France: the painter Goya and the poet Meléndez Valdés.